Establishing the Social and Legal Categories for “Girls” and “Girl Children” - Guercio, Laura (Violence against women, 2022)
This article examines whether a clearer lexical and conceptual distinction between the various stages of development, from birth to adulthood, is required to better recognize and protect the needs of the young female population affected by armed conflict. Using intersectional feminist theory, this analysis proposes a reflection on the use of a more precise definition and conceptualization of the term girls and girl children, as two distinct age stages with distinct physical and psychological development.